A Review of Pesticide Residues in Pears: Current Status, Dissipation Pattern and Detection Methods - Li Zhang; Tengfei Liu; Linlin Shi; Libin Wang; Daifeng Yang (Foods)
Pears are pome fruits widely cultivated and consumed globally due to their unique taste and flavor. The application of pesticides is a significant practice to combat pear pests and diseases across the world; however, pesticide use during production frequently results in undesirable residues in postharvest pear products, raising concerns about potential health impacts. Thus, the monitoring of pesticide residues (PRs) in pears has always been of great importance. To assess the degree of PRs in pears, sensitive and selective techniques are required to detect them. This review article attempts to provide readers with an overview of analytical methods utilized for the quantitative analysis of PRs in pears. Sample preparation and detection techniques are described and compared, and the advantages and disadvantages of these procedures are discussed. Furthermore, this paper elucidates the occurrence characteristics and dissipation patterns of PRs in pears through a comprehensive analysis of global research data on pear crops. In addition, potential trends for future research are presented, with the goal of contributing valuable insights to ongoing studies on PRs in pears and other fruits.